Plasticizer composition, resin composition and method for preparing the same

By blending terephthalate-based material with epoxidized oil, a plasticizer composition for PVC resin was prepared, which solved the problems of increased viscosity, reduced absorption rate and poor migration performance in PVC resin, and achieved excellent plasticization efficiency, migration performance and gelling performance.

CN107207865BActive Publication Date: 2025-03-07LG CHEM LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN201680006403.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2016-03-17
Filing Date
2016-03-18
Publication Date
2025-03-07
Estimated Expiration
2037-06-11

AI Technical Summary

Technical Problem

When used in PVC resins, existing plasticizers have problems such as increased viscosity, reduced absorption rate and poor migration performance, which is difficult to meet the performance requirements of industrial products such as floor materials and wallpapers.

Method used

A plasticizer composition is developed to prepare a plasticizer with excellent properties by blending a terephthalate-based material with epoxidized oil. The weight ratio of the composition can be between 99:1 and 1:99, and the specific choice is adjusted according to performance requirements.

Benefits of technology

The plasticizer composition can significantly improve plasticization efficiency, migration performance and gelling performance, provide excellent migration resistance and volatile resistance, and is suitable for the manufacture of various industrial products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0001354730790000051
    Figure GDA0001354730790000051
  • Figure GDA0001354730790000052
    Figure GDA0001354730790000052
  • Figure GDA0001354730790000053
    Figure GDA0001354730790000053
Patent Text Reader

Abstract

The present invention relates to a plasticizer composition, a resin composition, and a method for preparing the plasticizer composition, and provides a plasticizer and a resin composition containing the plasticizer by improving poor physical properties caused by structural limitations, wherein the plasticizer, when used as a plasticizer for the resin composition, can improve physical properties such as plasticizing efficiency, migration performance, tensile strength, elongation, stress migration and light stability required for sheet formulations.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0002] CROSS-REFERENCE TO RELATED APPLICATIONS

[0003] This application claims priority to and the benefit of Korean Patent Application No. 10-2015-0039000 filed in the Korean Intellectual Property Office on March 20, 2015, Korean Patent Application No. 10-2015-041793 filed in the Korean Intellectual Property Office on March 25, 2015, and Korean Patent Application No. 10-2016-0032374 filed in the Korean Intellectual Property Office on March 17, 2016, the entire contents of which are incorporated herein by reference. Technical Field

[0004] The present invention relates to a plasticizer composition, a resin composition and a method for preparing the same. Background Art

[0005] Among common plasticizers, alcohols react with polycarboxylic acids such as phthalic acid and adipic acid to obtain corresponding esters. In addition, considering the restrictions on phthalate-based plasticizers that are harmful to the human body at home and abroad, research on plasticizer compositions that can replace phthalate-based plasticizers, such as terephthalate-based plasticizers, adipic acid-based plasticizers and other polymer-based plasticizers, is in progress.

[0006] At the same time, in order to manufacture floor materials, wallpapers, sheet industrial products, etc., it is necessary to use appropriate plasticizers in consideration of discoloration, migration properties, processing properties, etc. Plasticizers, fillers, stabilizers, viscosity reducers, dispersants, defoamers, foaming agents, etc. are mixed with PVC resins according to the properties required by various industries in various applications such as tensile strength, elongation, light resistance, migration properties, gelling properties, processing properties, etc.

[0007] As an example, when relatively inexpensive dioctyl terephthalate is used in a plasticizer composition that can be used for PVC, the viscosity increases, the absorption rate of the plasticizer decreases relatively, and the migration property is not favorable.

[0008] Therefore, there is a need for continuous research into technologies that can be optimally used as plasticizers for vinyl chloride-based resins by developing products superior to existing dioctyl terephthalate or products containing new compositions of dioctyl terephthalate. Summary of the invention

[0009] Technical issues

[0010] In view of the above circumstances, while continuing research on plasticizers, the inventors of the present invention identified a plasticizer composition capable of improving poor physical properties due to structural limitations, and completed the present invention.

[0011] In other words, the object of the present invention is to provide a plasticizer, a method for preparing the plasticizer, and a resin composition containing the plasticizer, which, when used as a plasticizer for a resin composition, can improve the physical properties required when forming a sheet, etc., such as plasticizing efficiency, migration performance and gelling performance.

[0012] Technical Solution

[0013] One embodiment of the present invention provides a plasticizer composition, comprising: a terephthalate-based material; and epoxidized oil, wherein a weight ratio of the terephthalate-based material to the epoxidized oil is 99:1 to 1:99.

[0014] A weight ratio of the terephthalate-based material to the epoxidized oil may be 95:5 to 50:50.

[0015] A weight ratio of the terephthalate-based material to the epoxidized oil may be 90:10 to 50:50.

[0016] The terephthalate-based material can be any one selected from di(2-ethylhexyl) terephthalate (DEHTP or DOTP), diisononyl terephthalate (DINTP), dibutyl terephthalate (DBTP), butyl isononyl terephthalate (BINTP), butyl (2-ethylhexyl) terephthalate (BEHTP or BOTP) and (2-ethylhexyl) isononyl terephthalate (EHINTP or OINTP).

[0017] The terephthalate-based material may be di(2-ethylhexyl) terephthalate or diisononyl terephthalate.

[0018] The epoxidized oil may include at least one selected from the group consisting of epoxidized soybean oil, epoxidized castor oil, epoxidized linseed oil, epoxidized palm oil, epoxidized stearic acid, epoxidized oleic acid, epoxidized tall oil, and epoxidized linoleic acid.

[0019] The plasticizer composition may further include an additive, and the additive may include an acetyl citrate-based material, a trimellitate-based material, or a mixture thereof.

[0020] The additive may be included in an amount of 1 part by weight to 100 parts by weight, based on 100 parts by weight of the plasticizer composition.

[0021] The acetyl citrate-based material may include at least one selected from the group consisting of mixed C4-C9 alkyl-substituted acetyl citrate and non-mixed C4-C9 alkyl-substituted acetyl citrate.

[0022] The trimellitate-based material may include at least one selected from the group consisting of tributyl trimellitate (TBTM), triisononyl trimellitate (TINTM), and tri(2-ethylhexyl) trimellitate (TOTM or TEHTM).

[0023] Another embodiment of the present invention provides a method for preparing a plasticizer composition, the method comprising: providing a terephthalate-based material and an epoxidized oil; and blending the terephthalate-based material and the epoxidized oil in a weight ratio of 99:1 to 1:99 to prepare the plasticizer composition.

[0024] After blending to prepare the plasticizer composition, the method may further include mixing 1 to 100 parts by weight of an additive based on 100 parts by weight of the plasticizer composition.

[0025] Another embodiment of the present invention provides a resin composition comprising: 100 parts by weight of a resin; and 5 to 150 parts by weight of the plasticizer composition according to claim 1 .

[0026] The resin may be at least one selected from ethylene vinyl acetate copolymer, polyethylene, polypropylene, polyketone, polyvinyl chloride, polystyrene, polyurethane, and thermoplastic elastomer.

[0027] The resin composition may be a material for at least one selected from the group consisting of a wire material, a floor material, an automobile interior material, a film, a sheet material, a wallpaper, and a pipe material.

[0028] Beneficial Effects

[0029] When used in a resin composition, the plasticizer composition according to one embodiment of the present invention may provide excellent properties such as migration resistance and volatility resistance, as well as excellent plasticization efficiency, tensile strength, and elongation. DETAILED DESCRIPTION

[0030] Best Mode for Carrying Out the Invention

[0031] Example

[0032] Hereinafter, the present invention will be described in detail with reference to embodiments. However, embodiments according to the present invention may be modified into various other forms, and the scope of the present invention should not be construed as being limited to the embodiments described below. Embodiments of the present invention are provided to more fully describe the present invention to those with average knowledge levels in the art.

[0033] Preparation Example 1: Preparation of DOTP

[0034] 498.0 g of purified terephthalic acid (TPA), 1170 g of 2-ethylhexanol (2-EH) (the molar ratio of TPA:2-EH was 1.0:3.0) and 1.54 g of a titanium catalyst (TIPT, tetraisopropyl titanate) (0.31 parts by weight based on 100 parts by weight of TPA) were added to a 4-neck 3-liter reactor equipped with a cooler, a condenser, a decanter, a reflux pump, a temperature controller, a stirrer, etc., and the temperature was slowly increased to about 170° C. Water began to be generated at approximately 170° C., and an esterification reaction was performed for about 4.5 hours at a reaction temperature of about 220° C. under atmospheric pressure while continuously adding nitrogen, and the reaction was completed when the acid value reached 0.01.

[0035] After the reaction is completed, extractive distillation is carried out under reduced pressure for 0.5 to 4 hours to remove unreacted raw materials. Steam distillation is carried out under reduced pressure for 0.5 to 3 hours with steam to remove unreacted raw materials to a certain content level, and after the reaction solution is cooled to about 90°C, neutralization is carried out with an alkaline solution. In addition, water rinsing can be additionally performed, and then moisture is removed by dehydrating the reaction solution. A filter medium is added to the reaction solution to remove moisture, and the resultant is stirred for a period of time, and then filtered to finally obtain 1326.7g of di(2-ethylhexyl)terephthalate (yield: 99.0%).

[0036] Preparation Example 2: Preparation of DINTP

[0037] DINTP was prepared in the same manner as in Preparation Example 1, except that isononanol was used instead of 2-ethylhexanol in the esterification reaction.

[0038] Preparation Example 3: Preparation of TOTM

[0039] 384.2 g of trimellitic acid and 1171 g of octanol were used as reaction raw materials to finally produce 1071 g of trioctyl trimellitate (yield: 98%).

[0040] Preparation Example 4: Preparation of TINTM

[0041] 384.2 g of trimellitic acid and 1230 g of isononanol were used as reaction raw materials to finally prepare 1154 g of triisononyl trimellitate (yield: 98%).

[0042] Preparation Example 5: Preparation of TBTM

[0043] 576.3 g of trimellitic acid and 1000 g of butanol were used as reaction raw materials to finally produce 1124 g of tributyl trimellitate (yield: 99%).

[0044] Preparation Example 6: Preparation of ATOC

[0045] 384 g of citric acid and 1014 g of 2-ethylhexanol were used as reaction raw materials to obtain 1029 g of trioctyl citrate (tri(2-ethylhexyl) citrate) (yield 98%). 214 g of acetic anhydride was used for the trioctyl citrate obtained above to finally obtain 1119 g of acetyl trioctyl citrate (yield: 98%).

[0046] Preparation Example 7: Preparation of ATBC

[0047] 384g of citric acid and 1000g of butanol were used as reaction raw materials to obtain 706g of tributyl citrate (yield: 98%). 214g of acetic anhydride was used for the tributyl citrate obtained above to finally obtain 789g of acetyl tributyl citrate (yield: 98%).

[0048] The plasticizer compositions of Examples 1 to 4 were prepared using the materials prepared in Preparation Examples 1 to 7 and the epoxidized oil, and the preparations are summarized in the following Tables 1 to 4. The physical properties of the plasticizer compositions were evaluated according to the following test items.

[0049]

Table 1

[0050]

[0051]

Table 2

[0052]

[0053]

Table 3

[0054]

[0055]

Table 4

[0056]

[0057] <Test Item>

[0058] The measurement conditions of the following test items may be for the illustrative purpose of describing the measurement method, and reference may be made to specific measurement and evaluation conditions of test examples employing other conditions in individual test examples.

[0059] Determination of hardness

[0060] The Shore hardness at 25°C, 3T 10s was measured according to ASTM D2240.

[0061] Determination of tensile strength

[0062] According to the method of ASTM D638, the point at which the sample breaks is measured after being stretched at a crosshead speed of 200 mm / min (1 T) using a tester UTM (manufacturer: Instron, model: 4466). The tensile strength is calculated as follows:

[0063] Tensile strength (kgf / mm 2 ) = load value (kgf) / thickness (mm) × width (mm)

[0064] Determination of elongation

[0065] After being stretched at a crosshead speed of 200 mm / min (1 T) using a tester UTM according to the method of ASTM D638, the point at which the sample breaks is determined. The elongation is calculated as follows:

[0066] Elongation (%) = length after elongation / initial length × 100.

[0067] Determination of tensile strength and elongation retention

[0068] The determination of tensile and elongation retention determines the tensile and elongation properties remaining on the sample after heat is applied for a certain period of time at a specific temperature, and the determination method is the same as the method for determining tensile strength and elongation.

[0069] Determination of migration loss

[0070] A sample with a thickness of 2 mm or more was prepared according to KSM-3156. After a PS plate was attached to both sides of the sample, a 1 kgf / cm 2 The sample was placed in a forced convection oven (80°C) for 72 hours, then taken out and cooled at room temperature for 4 hours. After that, the PS plates attached to both side surfaces of the sample were removed, the weights of the sample before and after being placed in the oven were measured, and the amount of migration loss was calculated by the following equation.

[0071] Amount of migration loss (%) = [(initial weight of sample at room temperature - weight of sample after being left in oven) / initial weight of sample at room temperature] × 100

[0072] Determination of Volatilization Loss

[0073] After processing the prepared sample at 80° C. for 72 hours, the weight of the sample was measured.

[0074] Volatilization loss (%) = [(weight of initial sample - weight of processed sample) / weight of initial sample] × 100.

[0075] Determination of absorption rate

[0076] The absorption rate was evaluated such that the resin and the ester compound were mixed with each other using a Planatary mixer (Brabender, P600) under the conditions of 77 and 60 rpm, and the time taken for the torque of the mixer to become stable was measured.

[0077] Stress testing

[0078] For stress testing, the sample is left in a bent state for a certain period of time, and the degree of migration (bleeding) is observed and expressed as a number. Numbers closer to 0 indicate excellent performance.

[0079] Determination of light fastness

[0080] The samples were placed in a QUV and subjected to UV radiation for 200 hours according to the method of ASTM 4329-13, and then the color change was calculated using a reflectometer.

[0081] Determination of heat resistance

[0082] The degree of color change of the initial sample and the sample after the volatility reduction test using the volatility reduction determination method is determined by using the change in the E value of the colorimeter relative to the L, a and b values.

[0083] Determination of cold resistance

[0084] Five of the prepared samples were left to stand at a specific temperature for 3 minutes and then struck, and the temperature at which three of the five samples were destroyed was measured.

[0085] Experimental Example 1: DOTP-based plasticizer composition

[0086] Mixed plasticizer compositions were prepared by mixing DOTP with ESO or ELO in the mixing ratios of Examples 1-1 to 1-5 listed in Table 1 and used as samples for testing.

[0087] For the preparation of the sample, referring to ASTM D638, 50 parts by weight of the mixed plasticizer composition and 3 parts by weight of a stabilizer (BZ153T) were mixed into 100 parts by weight of PVC in a 3L super mixer at 98°C and 700rpm, and then a 5 mm sheet was prepared by processing the resultant at 160°C for 4 minutes using a roll mill, and then a 1 mm to 3 mm sheet was prepared by pressing the resultant at low pressure for 2.5 minutes and at high pressure for 2 minutes at 180°C. Physical properties were evaluated using each sample with each evaluation item as described above, and the results are summarized in the following Table 5.

[0088]

Table 5

[0089]

[0090] *Hardness: 3T, 10s

[0091] *Tensile strength and elongation: 1T, 200mm / min

[0092] *Migration loss: 80℃, 1T, 1kgf / cm 2 , 72 hours

[0093] *Volatilization loss: 100℃, 72 hours

[0094] *Absorption rate: 88℃

[0095] *Stress test: 23℃, 168 hours

[0096] As shown in Table 5, it was confirmed that the plasticizer compositions of Examples 1-1 to 1-5 prepared by mixing epoxidized oil with DOTP (a terephthalate-based material) showed equal or higher levels in physical properties such as tensile strength, hardness, elongation or volatility reduction, and showed equal or higher improved physical properties in migration loss, stress resistance and elongation, compared with the existing DOTP plasticizer of Comparative Example 1.

[0097] As described above, it was confirmed that when a plasticizer composition is prepared by mixing a terephthalate-based material with an epoxidized oil, the plasticizer composition can improve migration loss or resistance to stress while having the same or higher levels of basic physical properties of the plasticizer.

[0098] In addition, when the plasticizer composition contains a relatively small amount of epoxidized oil, the plasticizer composition may not be suitable for the use of the plasticizer composition in terms of absorption rate, volatility reduction or stress test results, and therefore, in order to distinguish the epoxidized oil from the epoxidized oil used as an auxiliary stabilizer, containing the epoxidized oil at 5 wt % or more, preferably 10 wt % or more, and optimally 20 wt % or more may be suitable for practical use of the plasticizer.

[0099] Test Example 2: DINTP-based plasticizer composition

[0100] Mixed plasticizer compositions were prepared by mixing DINTP with ESO or ELO in the mixing ratios of Examples 2-1 to 2-5 listed in Table 2 and used as test samples. The conditions for the preparation of the samples and the evaluation of physical properties were the same as those of Test Example 1, and the results are shown in Table 6 below.

[0101]

Table 6

[0102]

[0103] As shown in Table 6, it was confirmed that the plasticizer compositions prepared by mixing the epoxidized oil with DINTP (a terephthalate-based material) of Examples 2-1 to 2-5 showed equal or higher levels in physical properties such as tensile strength, hardness, volatility loss, and elongation compared to the existing DOTP plasticizer of Comparative Example 1, and showed equal or higher improved physical properties in migration loss, stress resistance, elongation, and tensile strength properties compared to Comparative Example 1.

[0104] As described above, it was confirmed that when a plasticizer composition is prepared by mixing a terephthalate-based material with an epoxidized oil, the plasticizer composition can improve migration loss or resistance to stress while having the same or higher levels of basic physical properties of the plasticizer.

[0105] In addition, when the plasticizer composition contains a relatively small amount of epoxidized oil, the plasticizer composition may not be suitable for the use of the plasticizer composition in terms of absorption rate, volatility reduction or stress test results, and therefore, in order to distinguish the epoxidized oil from the epoxidized oil used as an auxiliary stabilizer, the epoxidized oil contained at 5 wt % or more, preferably 10 wt % or more, and optimally 20 wt % or more may be suitable for practical use of the plasticizer.

[0106] Experimental Example 3: Mixed plasticizer composition of DOTP, ESO and trimellitate-based material

[0107] Mixed plasticizer compositions were prepared by mixing DOTP and ESO with each of TOTM, TINTM and TBTM as additives in the mixing ratios of Examples 3-1 to 3-9 and Comparative Example 3-1 listed in Table 3 and used as samples for testing.

[0108] For the preparation of the sample, referring to ASTM D638, 50 parts by weight of the mixed plasticizer composition, 40 parts by weight of filler (OMYA1T), 5 parts by weight of stabilizer (RUP-144) and 0.3 parts by weight of lubricant (St-A) were mixed into 100 parts by weight of PVC in a 3L super mixer at 98°C and 700rpm to prepare the sample, and the mixture was prepared by processing the resultant at 160°C for 4 minutes using a roll mill, and then the resultant was pressed at low pressure for 2.5 minutes and at high pressure for 2 minutes at 180°C. Physical properties were evaluated using each sample in each evaluation item as described above, and the results are summarized in the following Table 7.

[0109]

Table 7

[0110]

[0111] *Hardness: 3T, 10s

[0112] *Tensile strength and elongation: 1T, 200mm / min

[0113] *Tensile retention and elongation retention: 121℃, 168 hours

[0114] *Migration loss: 80℃, 1T, 1kgf / cm 2 , 72 hours

[0115] * Volatilization loss: 113℃, 168 hours

[0116] *Stress test: 23℃, 168 hours

[0117] As shown in Table 7, it was confirmed that the plasticizer compositions prepared by mixing the epoxidized oil with DOTP (a terephthalate-based material) and further adding TOTM, TINTM and TBTM among trimellitate-based materials as additives in Examples 3-1 to 3-9 showed equal or higher levels in physical properties such as tensile strength, volatility loss, migration loss and elongation compared to the existing DIDP plasticizer of Comparative Example 1.

[0118] In addition, considering that even when Examples 3-1 to 3-9 are mixed plasticizer compositions containing 20% ​​by weight or more of epoxidized oil, physical properties such as hardness or tensile strength are more excellent than DIDP (an existing plasticizer), it is indirectly confirmed that the effect is caused by the additive. When Examples 3-1 to 3-9 are compared with Comparative Example 3-1 in which the additive content exceeds 100 parts by weight, it is determined that when too much additive is contained, physical properties such as plasticizing efficiency, tensile strength, tensile retention, elongation, and elongation retention may be reduced.

[0119] The existing DIDP plasticizer has excellent physical properties, but its use is limited due to environmental issues. By additionally adding a trimellitic acid ester-based material, it is confirmed that a plasticizer composition that can replace the existing DIDP plasticizer in the field of compound industry can be provided.

[0120] Experimental Example 4: Mixed plasticizer composition of DOTP, ESO and acetyl citrate-based material

[0121] Mixed plasticizer compositions were prepared by mixing DOTP and ESO with each of ATOC and ATBC as additives in the mixing ratios of Examples 4-1 to 4-8 and Comparative Example 4-1 listed in Table 4, and used as test samples. The preparation of the samples and the evaluation of physical properties were the same as in Test Example 1, and the results are shown in Table 8 below.

[0122]

Table 8

[0123]

[0124] As shown in Table 8, it was confirmed that the plasticizer compositions prepared by mixing the epoxidized oil with DOTP (a terephthalate-based material) and further adding ATOC and ATBC of the acetyl citrate-based material as additives of Examples 4-1 to 4-8 showed equal or higher levels in physical properties such as tensile strength, volatilization loss, migration loss, and elongation compared to the existing DIDP plasticizer of Comparative Example 1.

[0125] In addition, considering that even when Examples 4-1 to 4-8 are mixed plasticizer compositions containing 20% ​​by weight or more of epoxidized oil, physical properties such as hardness or tensile strength are more excellent than DIDP (an existing plasticizer), it is indirectly confirmed that the effect is caused by the additive. When Examples 4-1 to 4-8 are compared with Comparative Example 4-1 in which the additive content exceeds 100 parts by weight, it is determined that when too much additive is contained, physical properties such as plasticization efficiency, elongation, and tensile retention may be reduced.

[0126] The existing DIDP plasticizer has excellent physical properties, but its use is limited due to environmental issues. By additionally adding an acetyl citrate-based material, it is confirmed that a plasticizer composition that can replace the existing DIDP plasticizer in the field of compound industry can be provided.

[0127] However, acetyl tributyl citrate has a relatively small molecular weight and has problems in improving physical properties such as migration loss or volatilization loss, and in view of the above, it is confirmed that adding a material having a high molecular weight as an additive is more desirable in the compound industry. Compared with the case of adding other materials as additives, additives having a small molecular weight can have more excellent elongation, hardness, etc. in addition to migration loss and volatilization loss, and it can be seen that in industries other than the wire compound industry that emphasizes physical properties such as volatilization loss, such as rolled plates and floor materials with simpler process conditions, acetyl tributyl citrate can have advantages in productivity and processability, such as excellent plasticizing efficiency.

[0128] Hereinabove, preferred embodiments of the present invention are described in detail, however, the scope of the present invention is not limited thereto, and various modifications and improvements of the basic concept of the present invention defined in the claims by those skilled in the art are also included in the scope of the present invention.

[0129] Embodiments of the present invention

[0130] Hereinafter, the present invention will be described in detail.

[0131] Firstly, the technical feature of the present invention is to provide a plasticizer composition capable of improving poor physical properties caused by structural limitations.

[0132] According to one embodiment of the present invention, a plasticizer composition containing a terephthalate-based material may be provided. Specifically, the terephthalate-based material may be contained in an amount selected from the range of 1 wt % to 99 wt %, 20 wt % to 99 wt %, 40 wt % to 99 wt %, 50 wt % to 95 wt %, 60 wt % to 90 wt %, etc., based on the total weight of the composition.

[0133] As an example, the terephthalate-based material may have terminal groups independently selected from C1-C12 alkyl, C3-C11 alkyl, C4-C10 alkyl, C8-C10 alkyl, C8-C9 alkyl, or C8 alkyl.

[0134] The terephthalate-based material can be any one selected from di(2-ethylhexyl) terephthalate (DEHTP or DOTP), diisononyl terephthalate (DINTP), dibutyl terephthalate (DBTP), butyl isononyl terephthalate (BINTP), butyl (2-ethylhexyl) terephthalate (BEHTP or BOTP) and (2-ethylhexyl) isononyl terephthalate (EHINTP or OINTP).

[0135] More preferably, the terephthalate-based material may be di(2-ethylhexyl) terephthalate or diisononyl terephthalate.

[0136] In addition, according to one embodiment, the plasticizer composition may further include epoxidized oil, and for example, the epoxidized oil may include epoxidized soybean oil, epoxidized castor oil, epoxidized linseed oil, epoxidized palm oil, epoxidized stearic acid, epoxidized oleic acid, epoxidized tall oil, epoxidized linoleic acid, or a mixture thereof.

[0137] Here, in the plasticizer composition, the weight ratio of the terephthalate-based material to the epoxidized oil may be 99:1 to 1:99. The weight ratio of the terephthalate-based material to the epoxidized oil may be 99:1 to 20:80, 99:1 to 40:60, 99:1 to 50:50, or 99:1 to 60:40. And preferably, the weight ratio of the terephthalate-based material to the epoxidized oil may be 95:5 to 50:50, 90:10 to 50:50, or 90:10 to 60:40.

[0138] When the amount of the epoxidized oil added is increased, the migration resistance and absorption rate to stress may become excellent. Physical properties such as tensile strength or elongation may be slightly decreased, but still included in the required physical property range. Therefore, the required physical properties can be freely controlled by adjusting the content of the epoxidized oil, and the epoxidized oil can be appropriately used according to the use of the vinyl chloride-based resin composition.

[0139] In addition, the epoxidized oil may be preferably contained at about 10 wt % or more, more preferably 20 wt % or more, based on the total amount of the plasticizer composition.

[0140] Generally speaking, epoxidized oil is sometimes included as a stabilizer when preparing a plasticizer, however, this can be distinguished from the epoxidized oil used as the second plasticizer described above. Compared to phthalate-based materials, such as diisodecyl phthalate, which has been used as a plasticizer in the art, the use of the terephthalate-based materials as the first plasticizer is more environmentally friendly, however, it may be difficult to achieve a level suitable for commercialization in terms of economic feasibility or existing physical properties, and the addition of epoxidized oil at the level of stabilizer may make it difficult to approach the physical properties achieved by existing plasticizers.

[0141] However, when 20 wt % or more of the epoxidized oil is used, migration resistance or absorption performance may become excellent, absorption speed may be particularly excellent, and physical properties such as tensile strength or elongation may be equal to or better than those of existing phthalate-based plasticizers.

[0142] The plasticizer composition includes a terephthalate-based material and an epoxidized oil, and may further include additives. The additives may be included in an amount of 1 to 100 parts by weight, preferably 1 to 80 parts by weight, based on 100 parts by weight of the plasticizer composition.

[0143] The additive may be mixed with the terephthalate-based material alone and improve stress characteristics of the resin composition, etc., however, even if a small amount of the additive is mixed and included in the plasticizer composition, a compound having excellent physical properties, etc. may be prepared. When a larger amount of the additive is included, the physical properties of the plasticizer composition may be out of control in controlling physical properties suitable for application, and problems such as excessive improvement of undesirable physical properties or reduction of desired physical properties may occur.

[0144] Specifically, in a mixed plasticizer composition of a terephthalate-based material and an epoxidized oil, if the epoxidized oil is excessively contained, the content of the terephthalate-based material is relatively low. In this case, among various physical properties, a physical property such as plasticizing efficiency related to processability may not be relatively excellent. And this property can be compensated by further adding an additive.

[0145] When an acetyl citrate-based material, a trimellitic acid ester-based material or a mixture thereof is used as the additive, a large amount of empty space can be formed in the plasticizer composition due to the large steric hindrance of the material, and therefore, additional effects such as improved processing performance can be achieved, and preferably, adding a material with a smaller molecular weight to the additive can be more helpful in improving processing performance.

[0146] The acetyl citrate-based material may include at least one compound selected from the group consisting of a mixed C4-C9 alkyl-substituted acetyl citrate-based material and a non-mixed C4-C9 alkyl-substituted acetyl citrate-based material.

[0147] For example, the mixed C4-C9 alkyl substituted acetyl citrate-based material can be a citrate ester having a combination of C4-C8 alkyl substituents, such as 2-acetylpropane-1,2,3-tricarboxylic acid 1,2-dibutyl 3-(2-ethylhexyl) ester, 2-acetylpropane-1,2,3-tricarboxylic acid 1,3-dibutyl 2-(2-ethylhexyl) ester, 2-acetylpropane-1,2,3-tricarboxylic acid 1-butyl 2,3-di(2-ethylhexyl) ester or 2-acetylpropane-1,2,3-tricarboxylic acid 1-butyl 2,3-di(2-ethylhexyl) ester. 2,3-tricarboxylic acid 2-butyl ester 1,3-di(2-ethylhexyl) ester; acetyl citrate esters with a combination of alkyl substituents of 5 and 7 carbon atoms, such as 2-acetylpropane-1,2,3-tricarboxylic acid 1,2-dipentyl ester 3-heptyl ester, 2-acetylpropane-1,2,3-tricarboxylic acid 1,3-dipentyl ester 2-heptyl ester, 2-acetylpropane-1,2,3-tricarboxylic acid 1-pentyl ester 2,3-diheptyl ester or 2-acetylpropane-1,2,3-tricarboxylic acid 2-pentyl ester 1,3-diheptyl ester, etc. In addition, the mixed C4-C9 alkyl-substituted acetyl citrate-based material can be acetyl citrate esters with a combination of two alkyl substituents containing different numbers of carbon atoms selected from 4 to 9, etc. The alkyl group can be linear or branched.

[0148] In the non-mixed C4-C9 alkyl substituted acetyl citrate-based material, the C4-C9 alkyl group may be linear or branched. For example, the non-mixed C4-C9 alkyl substituted acetyl citrate-based material may be acetyl tributyl citrate (ATBC), acetyl tripentyl citrate (ATPC), acetyl trihexyl citrate (ATHC), acetyl triheptyl citrate (ATHC), acetyl trioctyl citrate (ATOC), acetyl trinonyl citrate (ATNC), etc., and the butyl to nonyl groups may include various structural isomers, for example, isobutyl in the case of butyl, and 2-ethylhexyl in the case of octyl.

[0149] Although not limited thereto, non-heterogeneous C4-C9 alkyl substituted acetyl citrates may be preferred over heterogeneous alkyl substituted acetyl citrates, and acetyl citrate tri(2-ethylhexyl) ester may be employed somewhat more frequently.

[0150] However, when an acetyl citrate-based material is used as an additive, the use of the plasticizer may vary depending on the molecular weight, and when a material having a large molecular weight is used, physical properties of plasticizer exudation such as migration loss or volatilization loss can be compensated, and therefore, use in the compounding industry may be preferred, and in the case of a material having a small molecular weight, use in fields requiring excellent processing properties may be preferred.

[0151] Similar to the acetylcitrate-based material, the trimellitate-based material may include a non-mixed C4-C9 alkyl-substituted trimellitate-based material, and the C4-C9 alkyl may be linear or branched. For example, the trimellitate-based material may be tributyl trimellitate (TBTM), triisobutyl trimellitate (TiBTM), triethylhexyl trimellitate (TEHTM), triisononyl trimellitate (TINTM), etc.

[0152] As a method for preparing the plasticizer composition of the present invention, a blending method may be employed, and one example of the blending preparation method is shown below.

[0153] The plasticizer composition may be prepared by providing a terephthalate-based material and an epoxidized oil, and blending the terephthalate-based material and the epoxidized oil in a weight ratio of 99:1 to 1:99.

[0154] The terephthalate-based material may be prepared by direct esterification of terephthalic acid and an alcohol. The alcohol is at least one selected from 2-ethylhexanol, isononanol, butanol, and isobutanol.

[0155] In addition, the method may further include mixing 1 to 100 parts by weight of an additive based on 100 parts by weight of the plasticizer composition after blending to prepare the plasticizer composition, and the description thereof is as described above.

[0156] Here, the additive may include an acetyl citrate-based material, a trimellitate-based material, or a mixture thereof, and the description thereof is as described above.

[0157] Direct esterification can be performed by adding terephthalic acid to alcohol, then adding a catalyst, and reacting the resultant under a nitrogen atmosphere; removing unreacted alcohol and neutralizing unreacted acid; and dehydrating and filtering by vacuum distillation.

[0158] The alcohol used in the blending preparation method may be used in an amount of 150 to 500 mol %, 200 to 400 mol %, 200 to 350 mol %, 250 to 400 mol %, or 270 to 330 mol %, based on 100 mol % of terephthalic acid.

[0159] Meanwhile, for example, the catalyst used in the blending preparation method may include at least one selected from acid catalysts such as sulfuric acid, hydrochloric acid, phosphoric acid, nitric acid, p-toluenesulfonic acid, methanesulfonic acid, ethanesulfonic acid, propanesulfonic acid, butanesulfonic acid and alkylsulfuric acid, metal salts such as aluminum sulfate, lithium fluoride, potassium chloride, cesium chloride, calcium chloride, ferric chloride and aluminum phosphate, metal oxides such as heteropolyacids, natural / synthetic zeolites, cation and anion exchange resins, and organic metals such as tetraalkyl titanate and polymers thereof. As a specific example thereof, tetraalkyl titanate may be used as a catalyst.

[0160] The amount of catalyst used may vary depending on the type, and as an example, a homogeneous catalyst may be used in an amount of 0.01 wt % to 5 wt %, 0.01 wt % to 3 wt %, 1 wt % to 5 wt %, or 2 wt % to 4 wt %, based on 100 wt % of the total reactants, and a heterogeneous catalyst may be used in an amount of 5 wt % to 200 wt %, 5 wt % to 100 wt %, 20 wt % to 200 wt %, or 20 wt % to 150 wt %, based on the total weight of the reactants.

[0161] Here, the reaction temperature may be 180°C to 280°C, 200°C to 250°C, or 210°C to 230°C.

[0162] The direct esterification and the transesterification described below can also be used to prepare the above-mentioned mixed or non-mixed acetyl citrate-based material or trimellitate-based material. In this case, the acetyl citrate-based material can also be prepared as a mixed composition with a certain ratio, and the composition ratio of the obtained mixture can be controlled according to the adjustment of the alcohol content as the reaction raw material.

[0163] Except for this, when the acetyl citrate-based material or the trimellitate-based material is prepared by direct esterification or transesterification, the description used in the preparation of the terephthalate-based material can be used in the same manner.

[0164] The "ester exchange" used in the present invention refers to the reaction of an alcohol and an ester as shown in the following reaction formula 1 to exchange R" of the ester with R' of the alcohol:

[0165] [Reaction formula 1]

[0166]

[0167] According to one embodiment, when transesterification is performed, three ester compositions can be prepared by three situations, such as the alkoxy group of the alcohol attacks the carbon atoms of two ester (RCOOR") groups present in the ester-based compound; the alkoxy group of the alcohol attacks the carbon atom of one ester (RCOOR") group present in the ester-based compound; and no reaction occurs.

[0168] In addition, the transesterification has the advantages of not causing wastewater problems compared to the esterification reaction between an acid and an alcohol, and can be performed without a catalyst, thus being able to solve the problems caused by the use of an acid catalyst.

[0169] In addition, the composition ratio of the mixture obtained by the transesterification can be controlled according to the amount of alcohol added.

[0170] The amount of the alcohol added may be 0.1 to 89.9 parts by weight, specifically 3 to 50 parts by weight, and more specifically 5 to 40 parts by weight, based on 100 parts by weight of the ester.

[0171] For the ester, the molar fraction of the ester participating in the transesterification increases with the amount of alcohol added, and therefore, the content of the two ester compounds (products) in the mixture may increase, and therefore, the content of the corresponding unreacted ester compounds therein tends to decrease.

[0172] According to one embodiment of the present invention, the molar ratio of the ester and the alcohol as reactants can be, for example, 1:0.005-5.0, 1:0.05-2.5 or 1:0.1-1.0, and within these ranges, the effect of preparing an ester-based plasticizer composition having high process efficiency and excellent improvement in processing performance is obtained.

[0173] According to one embodiment of the present invention, the transesterification can be carried out at a reaction temperature of 120°C to 190°C, preferably 135°C to 180°C, and more preferably 141°C to 179°C for 10 minutes to 10 hours, preferably 30 minutes to 8 hours, and more preferably 1 hour to 6 hours. A mixture of esters having a target composition can be effectively obtained within the temperature and time ranges described above. Here, the reaction time can be calculated by the time to reach the reaction temperature after raising the temperature of the reactants.

[0174] The transesterification may be performed in the presence of an acid catalyst or a metal catalyst, in which case, an effect of a shorter reaction time is obtained.

[0175] Examples of the acid catalyst may include sulfuric acid, methanesulfonic acid, p-toluenesulfonic acid, and the like, and examples of the above-mentioned metal catalyst may include an organic metal catalyst, a metal oxide catalyst, a metal salt catalyst, or a metal itself.

[0176] An example of the metal component may be at least one selected from tin, titanium, and zirconium.

[0177] In addition, after the transesterification reaction, the transesterification may further include distilling unreacted alcohol and reaction by-products such as ester-based compounds to remove the unreacted alcohol and the reaction by-products.

[0178] One example of the distillation may include two-step distillation for separation of the alcohol and reaction by-products using a difference in boiling points.

[0179] As another example, the distillation may be a mixed distillation. In this case, the effect of obtaining the ester-based plasticizer composition relatively stably in the target composition is achieved. The mixed distillation means distilling unreacted alcohol and reaction by-products simultaneously.

[0180] The resin composition may contain 5 to 150 parts by weight, 40 to 100 parts by weight, or 40 to 50 parts by weight of the plasticizer composition based on 100 parts by weight of the resin. The resin is selected from ethylene vinyl acetate copolymer, polyethylene, polypropylene, polyketone, polyvinyl chloride, polystyrene, polyurethane, and thermoplastic elastomer. The resin composition is effective for all compound formulations, sheet formulations, and plastisol formulations.

[0181] As an example, the plasticizer composition may be used to manufacture wire materials, floor materials, automobile interior materials, films, sheets, wallpapers, and pipes.

Claims

1. A plasticizer composition comprising: a terephthalate-based material; Epoxidized oils, and An additive comprising a trimellitic acid ester-based material, in, The weight ratio of the terephthalate-based material to the epoxidized oil is 90:10 to 50:50, and the content of the epoxidized oil is 20 wt % or more based on the total amount of the plasticizer composition; Wherein, the terephthalate-based material is any one selected from di(2-ethylhexyl) terephthalate, dibutyl terephthalate, butyl isononyl terephthalate, butyl (2-ethylhexyl) terephthalate and (2-ethylhexyl) isononyl terephthalate, Wherein, the trimellitic acid ester-based material includes at least one selected from the group consisting of tri(2-ethylhexyl) trimellitic acid ester and triisononyl trimellitic acid ester. Wherein, the additive is included in an amount of 1 to 100 parts by weight based on 100 parts by weight of the total amount of the terephthalate-based material and the epoxidized oil.

2. The plasticizer composition according to claim 1, wherein The terephthalate-based material is di(2-ethylhexyl) terephthalate.

3. The plasticizer composition according to claim 1, wherein The epoxidized oil includes at least one selected from epoxidized soybean oil, epoxidized castor oil, epoxidized linseed oil, epoxidized palm oil, epoxidized stearic acid ester, epoxidized oleic acid ester, epoxidized tall oil and epoxidized linoleic acid ester.

4. A method for preparing the plasticizer composition according to claim 1, comprising: providing a terephthalate-based material and an epoxidized oil; blending the terephthalate-based material and the epoxidized oil in a weight ratio of 90:10 to 50:50, and the content of the epoxidized oil is 20 wt % or more based on the total amount of the plasticizer composition; as well as further blending an additive to obtain a plasticizer composition, the additive comprising a trimellitic acid ester-based material, Wherein, the terephthalate-based material is any one selected from di(2-ethylhexyl) terephthalate, dibutyl terephthalate, butyl isononyl terephthalate, butyl (2-ethylhexyl) terephthalate and (2-ethylhexyl) isononyl terephthalate, Wherein, the trimellitic acid ester-based material includes at least one selected from the group consisting of tri(2-ethylhexyl) trimellitic acid ester and triisononyl trimellitic acid ester. Wherein, the additive is included in an amount of 1 to 100 parts by weight based on 100 parts by weight of the total amount of the terephthalate-based material and the epoxidized oil.

5. The method for preparing a plasticizer composition according to claim 4, wherein: The terephthalate-based material is prepared by direct esterification of an alcohol and terephthalic acid, wherein the alcohol is selected from 2-ethylhexanol, isononanol, butanol and isobutanol.

6. A resin composition comprising: 100 parts by weight of resin; and 5 to 150 parts by weight of the plasticizer composition of claim 1.

7. The resin composition according to claim 6, wherein The resin is at least one selected from ethylene vinyl acetate copolymer, polyethylene, polyketone, polypropylene, polyvinyl chloride, polystyrene and polyurethane.

8. The resin composition according to claim 6, wherein The resin composition is a material for at least one selected from the group consisting of wire materials, floor materials, automobile interior materials, films, sheets, wallpapers, and pipes.

Citation Information

Patent Citations

  • Storage and programming method thereof

    KR1020150039000A

  • Trans-Clomiphene Formulations and Uses Thereof

    KR1020150041793A

  • Medium storage

    KR1020160032374A

  • Radiation stabilized PVC compositions, and method of making same

    US20140162045A1

  • Polymer compositions containing terephthalates

    CN102272215A